(untitled) (Boletin Médico de Postgrado, 2020)
The goal of this study is to evaluate the effects of cognitive restructuring on cognitive distortions in adolescents in grief over their parent’s death. A descriptive, cross-sectional, with quasi-experimental design was performed on 10 high school students of public and private institutions who lost one or both parents. An instrument of closed questions was designed with a reliability of 0.94. The results show that 35% of adolescents had cognitive distortions before the study (emotional reasoning, overgeneralization, dichotomous thinking and personalization); after therapy 25% persisted with these distortions. Regarding the dimension stimuli, 63% were affected by conversations about their deceased parents; after therapy, only 25% were still affected. Sadness and anger was detected in 63% of adolescents; after the application of the technique, these emotional expressions presented only in 48% of participants. The analysis of the data revealed the effectiveness of this technique to modify cognitive distortions in this group of adolescents.